The Relationship Between Role Stressors And Organizational Commitment - Yashaiya, Nadia Hezlin (2006)
Level of education is one of the measures of nations' wealth. Good quality graduates who are knowledgeable, adaptable and versatile to a great extent promised a realization of the nations' vision. Thus, this had caused a need to have committed lecturers who are responsible to produce such graduates. As a result, these lecturers faced role stressors in their workplace because there are many demands, expectations and workload that are at times unmanageable.